PEMBELAJARAN KONSTRUKTIVISME BERBANTU MEDIA VIDEO/ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS X MIPA 3 - J Juriah; Nengsih Juanengsih (EDUSAINS, 2016)
Abstract This research aimed to improve biology learning score through a constructivist learning assisted by video/animation on the concept of ecology. This research was a classroom action research (CAR) conducted in two cycles. The subjects were 31 students of class X of SMAN 3 MIPA 3 South Tangerang during the academic year of 2014/2015. The research instrument used was a multiple choice test and an observation sheet. The results showed that the average students’ score in the first cycle was 72.55 with 58% of students achieved the minimum standard of mastery learning (Ketuntatan Belajar Minimal KBM) and the average students’ score in the second cycle was 80.55 with 87% students achieved KBM. According to the results, it was concluded that constructivism learning assisted with video/animation could improve students learning outcomes particularly on the concept of ecology. Abstrak Penelitian ini bertujuan untuk meningkatkan hasil belajar biologi dengan pembelajaran konstruktivisme berbantu media video/animasi pada konsep Ekologi. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Subjek penelitian adalah 31 siswa kelas X MIPA 3 SMAN 3 Kota Tangerang Selatan tahun ajaran 2014/2015. Instrumen penelitian berupa tes pilihan ganda dan lembar observasi. Hasil penelitian menunjukkan pencapaian hasil belajar pada siklus I rerata 72.55 dengan jumlah yang mencapai Ketuntasan Belajar Minimal (KBM) 58%, pada siklus II rerata belajar 80.55 dengan KBM 87%. Dengan hasil ini dapat disimpulkan bahwa pembelajaran konstruktivisme berbantu media video/animasi dapat meningkatkan hasil belajar pada konsep Ekologi. Permalink/DOI: http://dx.doi.org/10.15408/es.v8i1.3801